Lexicon of musical theater - Ramírez Vargas, Cristhyna María de los Ángeles (2021)
Musical theater is an artistic genre based on theater, which integrates songs, choirs (with voice or instrumentals) and dances, which are combined with the purpose of telling stories. Since 1886, musical theater has become more and more famous in countries such as the United States, Cuba, Argentina, among others. However, in Peru, only in the last decade, it has become increasingly popular. The artists in this field use certain terms specific to their jobs, which generally have a different meaning from that found in the Dictionary of the Spanish Language (2019). This paper collects forty-six (46) words that have been recovered from interviews with artists dedicated to musical theater. This research is descriptive in nature and aims at defining the words of this lexicon using the lexicographic technique. Each term contains etymological information, grammatical marks, definition, examples of use and, in some cases, lexicographical notes.